Administrative overspending in Indonesian districts: The role of local politics - Bambang Suharnoko Sjahrir; Krisztina Kis-Katos; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2013)
We analyze the determinants of the excessive administrative spending of local governments in Indonesia. In an unbalanced panel data set of 399 districts for 2001-2009, we show that the proliferation of districts has not led to increased administrative spending; instead a lack of political accountability is responsible for this excess. The degree of political competition influences the level of administrative spending significantly; newly introduced direct elections of district heads, however, did not curtail the waste.
Keywords: D73; H76; H11; R51; 330; administrative expenditures; decentralization; direct elections; Indonesia